The effect of various polishing systems on the surface roughness of composite resins - Didem Atabek; Elif Sungurtekin Ekçi; Mehmet Bani; Nurhan Öztaş (Gazi University, 2016)
OBJECTIVE: The aim of this in vitro study was to evaluate the effect of three finishing and polishing systems on the surface roughness of nano-manufactured composite resins. MATERIALS AND METHOD: Nano-ceramic Ceram-X (Dentsply DeTrey, Konstanz, Germany), nano-filled Premise (Kerr Corporation, Orange, NJ, USA) and nano-filled Clearfil Majestic (Kuraray Medical Inc., Tokyo, Japan) composite resins were tested. Forty samples of each material were cured under matrix strips. The samples were then randomly assigned into four test groups: 1) unpolished; 2) polished with burs out of resin reinforced by zircon-rich glass fiber (Stainbuster, Abrasive Technology, Inc., Lewis Center, OH, USA); 3) polished with aluminum oxide impregnated polymer points (Enhance Finishing System, Dentsply Caulk, Milford, DE, USA) followed by diamond impregnated micro-polishing points (PoGo, Dentsply Caulk); and 4) polished with aluminum oxide disks (Sof-Lex, Dentsply Caulk). The sample surface roughness values (Ra) were determined using a profilometer, and the surfaces were observed under a scanning electron microscope. Data were analyzed using the Kruskal-Wallis test. RESULTS: No statistically significant differences in surface roughness were detected among the finishing and polishing systems (p>0.05). However, all finishing and polishing techniques created statistically rougher surfaces than the control group (p<0.05). The mean Ra values of the finishing and polishing systems were ranked as follows: Mylar strip < Enhance Finishing System+PoGo < Stainbuster < Sof-Lex. These findings were confirmed by scanning electron microscope photomicrographs. CONCLUSION: All polishing systems produced clinically acceptable surface roughness on the tested composite materials. The smoothest surfaces were achieved using the nano-ceramic composites with the Enhance Finishing System and PoGo.